2018
DOI: 10.21608/ejh.2018.4243.1018
|View full text |Cite
|
Sign up to set email alerts
|

Ameliorative Effect of Watermelon rind ingestion on the Pancreas of Diabetic Female Albino Rat (Histological, immunohistochemical and morphometric study).

Abstract: Introduction: Type II diabetes is a multifactorial metabolic disorder that affects more than 348 million people worldwide. The pathway of type II diabetes is characterized both by insulin resistance in muscle, fat, and liver in addition to a relative failure of pancreatic cells. CitrullusLanatus (Watermelon) is one of the few foods naturally rich in amino acids citrulline and lycopene which decrease serum glucose concentration in diabetic rats. Aim of the study:To study the structural changes in diabetic pancr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 31 publications
1
0
0
Order By: Relevance
“…Excessive deposition of collagen fibres was detected by Mallory's trichrome stain inspection of the diabetic group. These results coincide with El-Desouki et al [18] and Sorour et al [56] that revealed increased collagen fibres around the islands of Langerhans, the pancreatic acini, the blood vessels and intercalated ducts in the diabetic group. Pancreatic fibrosis may be caused by pancreatic stellate cells (PSCs).…”
Section: Discussionsupporting
confidence: 92%
“…Excessive deposition of collagen fibres was detected by Mallory's trichrome stain inspection of the diabetic group. These results coincide with El-Desouki et al [18] and Sorour et al [56] that revealed increased collagen fibres around the islands of Langerhans, the pancreatic acini, the blood vessels and intercalated ducts in the diabetic group. Pancreatic fibrosis may be caused by pancreatic stellate cells (PSCs).…”
Section: Discussionsupporting
confidence: 92%